NY-ESO-1 Protein Cancer Vaccine With Poly-ICLC and OK-432: Rapid and Strong Induction of NY-ESO-1-specific Immune Responses by Poly-ICLC. Issue 4 (May 2017) - Takeoka, Tomohira; Nagase, Hirotsugu; Kurose, Koji; Ohue, Yoshihiro; Yamasaki, Makoto; Takiguchi, Shuji; Sato, Eiichi; Isobe, Midori; Kanazawa, Takayuki; Matsumoto, Mitsunobu; Iwahori, Kota; Kawashima, Atsunari; et al.
Abstract : We conducted a clinical trial of a cancer vaccine using NY-ESO-1 protein with polyinosinic-polycytidylic acid-poly-L-lysine carboxymethylcellulose (poly-ICLC) and/or OK-432 against solid tumors. A total of 15 patients were sequentially enrolled in 4 cohorts. Patients in cohort 1 received NY-ESO-1 protein; cohort 2a received NY-ESO-1 protein+OK-432; cohort 2b received NY-ESO-1 protein+poly-ICLC; cohort 3 received NY-ESO-1 protein+OK-432+poly-ICLC with Montanide ISA-51. The endpoints of this trial were safety, NY-ESO-1 immune responses, and clinical response. Vaccine-related adverse events observed were fever and injection-site reaction (grade 1). Two patients showed stable disease after vaccination. NY-ESO-1 antibodies were observed in 4 patients at the baseline (sero-positive) and augmented in all patients after vaccination. Eleven patients showed a conversion of negative antibody responses at baseline to positive after vaccination (seroconversion). The seroconversions were observed in all 11 sero-negative patients by the fourth immunization; in particular, it was observed by the second immunization in patients with poly-ICLC, and these induced antibody responses were stronger than those in patients immunized without poly-ICLC. The number of NY-ESO-1–specific interferon (IFN)γ-producing T cells was increased in patients immunized with poly-ICLC and/or OK-432, and furthermore, the increase of IFNγ-producing CD8 T cells in patients immunized with poly-ICLC was significantly higher than that in patients without poly-ICLC. Nonspecific activations of T-cell or antigen presenting cells were not observed. Our present study showed that poly-ICLC is a promising adjuvant for cancer vaccines. Abstract : Supplemental Digital Content is available in the text.